Depuration and anatomical distribution of domoic acid in the surf clam Mesodesma donacium. (August 2015) - Álvarez, Gonzalo; Uribe, Eduardo; Regueiro, Jorge; Martin, Helena; Gajardo, Teresa; Jara, Lorena; Blanco, Juan
Abstract: In northern Chile, domoic acid (DA) has been detected in several bivalve species. In Mesodesma donacium, one of the most important commercial species for local fishermen, no information is available on depuration, or on the anatomical distribution of this toxin and its potential use as a palliative measure to minimize the consequences of ASP outbreaks. Deputation of DA is very fast in M. donacium, and can be adequately described by means of a two-compartment model. The estimated rates for the first and second compartments were 1.27 d −1 and 0.24 d −1, respectively, with a transfer rate between compartments of 0.75. Having high depuration rates protects this species from being affected by Pseudo-nitzschia blooms for an extended period of time. Taking this into account, the time in which the bivalves are unsafe for consumers is very short, and therefore the economic losses that could result by the DA outbreaks in local fisheries should be moderate. In relation to anatomical distribution, at least during the uptake phase, the toxin was evenly distributed within the soft tissues, with a total toxin burden corresponding to 27%, 32% and 41% for Digestive Gland (DG), Foot (FT) and Other Body Fractions (OBF), respectively. Since the contribution of each organ to the toxin concentration is a function of both weight contribution and toxin burden, the pattern of toxin distribution showed the following trend: "all other body fractions" (OBF) > Foot (FT) > Digestive Gland (DG). Thus, the highest concentration of DA, with a contribution close to 72%, corresponds to the edible tissues (OBF + FT), while the DG (non-edible tissue) only contributes the remaining 28%. Consequently, in view of the anatomical distribution of domoic acid in M. donacium, the elimination of the digestive gland does not substantially reduce the toxicity of the final product and therefore selective evisceration would not improve their quality for human consumption. Highlights: Mesodesma donacium depurates domoic acid fast. The depuration kinetics of domoic acid follows a two compartment model. High depuration rates make that Mesodesma donacium should not be affected by Pseudo-nitzschia blooms for a long time. Toxin is nearly distributed among the clam tissue in a nearly homogeneous way. In M. donacium, the elimination of the digestive gland could not reduce substantially the toxicity of the final product.